Теоретико-прикладні аспекти конфліктності поліцейських у сучасній вітчизняній психології - Горяінов, А. В.; Horiainov, A. V. (Габітус. - 2021. - Вип. 32. - С. 176-180, 2021)
Досліджено конфліктність поліцейських за різними критеріями, включаючи взаємодію із цивільним населенням, а також між колегами та керівництвом. Наведено види конфліктів у поліцейському середовищі й конфліктогенні фактори, які мають місце в правоохоронній діяльності. Викладено базові обґрунтування поліцейської конфліктології як теоретико-прикладної дисципліни, її теоретичну природу і практичне застосування знань цієї галузі.

This article is based on the scientific achievements of Ukrainian scientists and is an overview. It outlines scientific papers on conflict in the police environment as a psychological problem. The article examines the study of police conflict on various criteria, including interaction with the civilian population, as well as between colleagues and management. The types of conflicts in the police environment and conflict-causing factors that take place in law enforcement are also presented. In addition, this article presents the basic rationale for police conflictology as a theoretical and applied discipline, which allows to state both the theoretical nature and to note the practical application of knowledge in this field. We review theoretical scientific views and some statistics obtained from empirical research in the field of conflict in the police environment, as well as note the recommendations of researchers to address this issue. The aspects highlighted in the article can be useful to demonstrate the possibility of practical application of empirical data resulting from research on the problem of conflict in the police environment as a psychological problem. The information presented in this article can be a starting point for further development of domestic scientific thought in legal psychology as a science in general and police conflictology in particular, as well as in related fields of knowledge, which allows to trace the interest in conflict in the police environment. This article can be useful not only for practical psychologists working in the field of resolving conflicts in the legal field, but also for scientists who study current issues of legal psychology.

Исследована конфликтность полицейских по разным критериям, включая взаимодействие с гражданским населением, а также между коллегами и руководством. Представлены виды конфликтов в полицейской среде и конфликтогенные факторы, которые имеют место в правоохранительной деятельности. Изложены базовые обоснования полицейской конфликтологии как теоретико-прикладной дисциплины, ее теоретическая природа и практическое применение знаний этой области.
Theoretical and applied aspects of police conflictness in modern Ukrainian legal psychology
Горяінов, А. В. Теоретико-прикладні аспекти конфліктності поліцейських у сучасній вітчизняній психології / Горяінов А. В. // Габітус. - 2021. - Вип. 32. - С. 176-180. - DOI: https://doi.org/10.32843/2663-5208. 2021.32.31.
Keywords: Психологія. Рsychology. Психология; Наукові публікації. Scientific publications. Научные публикации; Юридична психологія. Legal psychology. Юридическая психология; Україна. Ukraine. Украина; поліцейські; police officers; полицейские; конфліктність; conflict; конфликтность; психологічні чинники; psychological factors; психологические факторы; поліцейська конфліктологія; police conflictology; полицейская конфликтология; професійна діяльність; professional activity; профессиональная деятельность